2006
DOI: 10.21236/ada458949
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Weighted Essentially Non-Oscillatory Scheme for Hyperbolic Conservation Laws

Abstract: We develop in this article an improved version of the fifth-order weighted essentially non-oscillatory (WENO) scheme. Through the novel use of higher order information already present in the framework of the classical scheme, new smoothness indicators are devised and we obtain a new WENO scheme with less dissipation than the classical WENO of Jiang and Shu [2], with the same computational cost, and a slightly better performance than the improved mapped version of Henrick et al [3]. We show that the enhancement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(96 citation statements)
references
References 6 publications
1
95
0
Order By: Relevance
“…In [2,3], the improved performance of the WENO-Z5 scheme over the WENO-JS5 scheme has been demonstrated conclusively in computing a higher resolution solution when solving hyperbolic conservation laws for both smooth and discontinuous solutions. In [4], the WENO-Z5 scheme has been shown, in comparison to the WENO-JS5 scheme, to allow a more flexible choice on the as a function of grid spacing x that will guarantee the formal order of convergence of the nonlinear scheme regardless of the critical points while maintaining the essentially non-oscillatory nature of the shock-capturing scheme.…”
Section: Remarkmentioning
confidence: 96%
See 1 more Smart Citation
“…In [2,3], the improved performance of the WENO-Z5 scheme over the WENO-JS5 scheme has been demonstrated conclusively in computing a higher resolution solution when solving hyperbolic conservation laws for both smooth and discontinuous solutions. In [4], the WENO-Z5 scheme has been shown, in comparison to the WENO-JS5 scheme, to allow a more flexible choice on the as a function of grid spacing x that will guarantee the formal order of convergence of the nonlinear scheme regardless of the critical points while maintaining the essentially non-oscillatory nature of the shock-capturing scheme.…”
Section: Remarkmentioning
confidence: 96%
“…The smoothness of a given substencil is measured by the smoothness indicators {β k } r −1 k=0 that measure the normalized Sobolev norm of all the derivatives of each local polynomial. The nonlinear weights ω k , such as the classical weights given in the classical WENO-JS scheme [8] and the optimal weights given in the improved WENO-Z scheme [2,3], used in the formation of the convex combination of the local polynomials at the cell interface, have been used extensively. It has been numerically demonstrated that the WENO finite difference scheme based on the improved WENO-Z scheme is less dissipative and has a higher resolution power than the classical WENO-JS scheme for a larger class of problems.…”
Section: Introductionmentioning
confidence: 99%
“…For a better accuracy, an improved fifth-order WENO method is used for reconstructing the left and right state values [11] . In the method, a high-order spatial accuracy is achieved by means of a reconstruction procedure, which avoids generating spurious oscillations near the discontinuities and at the same time maintains the uniformly high-order accuracy in the regions where the solution is smooth.…”
Section: High-order Spacial Discretizationmentioning
confidence: 99%
“…Therefore, this paper focuses on the use of an improved fifth-order spatially accurate weighted ENO (WENO) scheme [11] for capturing the vortices while minimizing the numerical dissipation. The WENO scheme proposed by Liu et al [12] and extended by Jiang and Shu (WENO-JS) [13] can obtain good convergence properties while keeping the robustness and uniformly high-order accuracy of the ENO schemes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation